Cross sections of the 89Y(p,γ) reaction relevant to the p process - Tsagari, P.; Kokkoris, M.; Skreti, E.; Demetriou, P.; Galanopoulos, S.; Karydas, A. G; Zarkadas, Ch.; Harissopulos, S.; Paradellis, T.; Kunz, R.; Hammer, J. W. (HNPS Advances in Nuclear Physics, 2019)
The cross section of the 89Y(p,7)90Zr reaction was determined at Ep=l.4-4.8 MeV via angle-integrated measurements carried out by means of a 4π Nal summing detector as well as via angular distribution measurements using an array of 4 HPGe detectors with 100% relative efficiency. The resulting cross sections vary from 0.5 to 5 mb. Astrophysical S factors and reaction rates have also been derived. A good agreement between the experimental rates and and the predictions of statistical theory has been found.